Penerapan Voice Over Pada Motion Graphic “Permohonan Pengusaha Kena Pajak” Di KPP Pratama Bogor - Yulanda Rizqi Ramadhini; Khairunnisa Hayyu Kusnadi; Salsabila Diba Cahyani; Amata Fami (Institut Nalanda, 2023)
Motion Graphics are used as a medium for communicating visually in the digital world. When making motion graphics, there are several aspects that need to be considered, one of which is voice over. The application of voice over greatly influences the final result of motion graphics because it requires a product that is informative, interesting and easy for the audience to understand. By implementing voice over, you can increase understanding of the message conveyed by the motion graphic. The manufacturing process uses the Research and Development method which starts from the stage of determining the concept idea, collecting materials, product manufacturing process, product testing, and distribution.